Africans and globalization : linguistic, literary, and technological contents and discontents - Ojó, Akinloyè; Traoré, Karim; Longe, Oyinlola (Lexington Books, 2017)
Africans and Globalization: Linguistic, Literary, and Technological Contents and Discontents considers the substance and dissatisfactions of globalization on Africa and its Diaspora. Although variously framed across disciplines, globalization has generally entailed non-milieu bound interactions, which alters the existence of its participants. The concerns about the impact of globalization have been raised in relation to Africa and have related to the helpful and deleterious effects. Increasingly, industrialization (without consideration of environmental impacts) and westernization (including erosion of Indigenous values) are perceived as synonymous with globalization. This multidisciplinary collection contends that in theory, globalization linked Africa with the world through trade and information sharing, thereby increasing development. This collection provides reflections based on contemporary research within the linguistic, literary, and technological areas of study. It illustrates that globalization is not a single process but rather a complex set of processes that seemingly operate in an oppositional manner. The collected works make for exciting appraisal as they highlight some of the contents and discontents of globalization across multiple areas of human endeavor in Africa and its diaspora.